Avaliação da presença da antineoplásico em água residuária de um hospital oncológico e do sistema de esgotamento sanitário municipal - Zampieri, Denise Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Anticancer drugs represent one of the classes of pharmaceuticals with the greatest potential to cause negative effects on the environment. Contamination of the environment with these drugs may occur from several sources, such as emissions from industry or direct disposal of pharmaceuticals in households, but the main source of cytostatic compounds in the environment occur through sewage emission or excreted fluids (feces and urine) of patients receiving treatment. In this study we analyzed the presence of the antineoplastic 5-fluorouracil (5-FU) and its quantification in the effluents originated from a large oncology hospital and in the local municipal wastewater system. We analyzed 10 samples obtained from a distinct collection site (A), from the effluents of the Barretos Cancer Hospital (HCB). Also, 5 samples were obtained from two different sites (B and C) in the effluent from the Sewage Treatment Plant in Barretos (ETEB), whose final destination is the stream known as Ribeirão Pitangueiras. Presence of 5FU was observed in concentrations ranging from 26.7 to 733 μg/L in all 10 samples of the wastewater originated at the HCB collected at site A. These results were far superior to those found in similar studies performed at other hospitals. The predicted concentrations of the cytostatic agent in the wastewater from HCB was calculated using parameters such as 5-FU consumption, water consumption and the fraction of drug excreted unmetabolized. We found a low correlation between the predicted concentrations and the measured concentrations. This low recovery rate may have occurred due to probable excretion of the drug occuring outside the hospital facilities, since the majority of the patients were ambulatory. Other possibilities are drug degradation due to instability of the molecule and loss of a portion of the drug adsorbed in suspended solid matter of the effluent. The possible impact of the emission of 5-FU to the ...

Os medicamentos antineoplásicos são uma das classes de produtos farmacêuticos com maior potencial para causar efeitos negativos no ambiente. Várias fontes contribuem para a potencial contaminação do ambiente com esses medicamentos, como emissões da indústria ou descarte direto de produtos farmacêuticos nos domicílios, mas a principal fonte de compostos citostáticos no esgoto ou no ambiente são excreções (urina e fezes) de pacientes em tratamento. Neste estudo foi analisada a presença do antineoplásico 5-fluorouracil (5-FU) e sua quantificação nos efluentes de um hospital oncológico de grande porte e na rede municipal de tratamento de esgoto. Foram analisadas 10 amostras obtidas de um ponto distinto (A), a partir dos efluentes do Hospital de Câncer de Barretos (HCB) e 5 amostras foram obtidas de dois pontos diferentes (B e C) do efluente da Estação de Tratamento de Esgoto (ETE) da cidade de Barretos (ETEB), que tem como destino final o Ribeirão Pitangueiras. Observou-se a presença do fármaco na concentração de 26,7 a 733 μg/L em todas as 10 amostras de água residuária do HCB analisadas, os resultados foram muito superiores aos encontrados em outros trabalhos semelhantes realizados em outros hospitais. Também foi realizado o cálculo das concentrações previstas do agente citostático na água residuária do HCB, utilizando-se parâmetros como o consumo de 5-FU, o consumo de água e a fração de droga excretada na forma não metabolizada. Encontrou-se uma baixa correlação entre a concentração prevista e a concentração medida analiticamente. Esse baixo índice de recuperação pode ter ocorrido decorrente da excreção do fármaco realizada fora do ambiente hospitalar, de uma possível degradação da droga decorrente da instabilidade da molécula ou a perda de uma porção da droga adsorvida na matéria em suspensão dos efluentes. O impacto do descarte de 5-FU no meio ambiente foi avaliado através ...
Keywords: Agentes antineoplasicos; Medicamentos; Esgotos; Águas residuais - Purificação; Efluente - Qualidade; Hospitais; Sewage Purification